Investigating Droop Control Contribution to Grid Resilience by Maintaining Frequency Stability During Grid Disturbances - Anyangwe, C. N.; Anyanwu, C. N.; Udanor, C. (Transactions on Engineering and Computing Sciences, 2025)
In contrast to conventional power plants, which are based on large synchronous generators with large inertia capabilities to dampen sudden disturbances, renewable energy sources, such as solar and wind, connected to the grid through power electronics converters, display low system inertia and overload limiting capabilities. Additionally, because they lack primary frequency regulation capabilities, they are unable to actively respond to the frequency response of the system. This research investigates the contribution of droop control strategies to grid resilience by focusing on their ability to maintain frequency stability during grid disturbances. The study employs a simulation-based approach using MATLAB/Simulink to model the Djoum power plant in Cameroun and implement droop control algorithm. The methodology involves designing and analyzing the system's response under sudden load changes using droop and supervisory control strategies. Parameters such as droop coefficients and control bandwidths were systematically varied to analyze their impact on frequency regulation and grid resilience. Results show that droop control maintains system operation by adjusting frequency and voltage under disturbance, while supervisory control acts as a secondary layer to fully restore parameters to their reference values thereby ensuring reliable operation during grid disturbances.